Case Study in 21st‐Century Ecotoxicology: Using In Vitro Aromatase Inhibition Data to Predict Reproductive Outcomes in Fish In Vivo. (28th November 2022) - Villeneuve, Daniel L.; Blackwell, Brett R.; Blanksma, Chad A.; Cavallin, Jenna E.; Cheng, Wan‐Yun; Conolly, Rory B.; Conrow, Kendra; Feifarek, David J.; Heinis, Larry J.; Jensen, Kathleen M.; Kahl, Michael D.; Milsk, Rebecca Y.; et al.
Abstract: To reduce the use of intact animals for chemical safety testing, while ensuring protection of ecosystems and human health, there is a demand for new approach methodologies (NAMs) that provide relevant scientific information at a quality equivalent to or better than traditional approaches. The present case study examined whether bioactivity and associated potency measured in an in vitro screening assay for aromatase inhibition could be used together with an adverse outcome pathway (AOP) and mechanistically based computational models to predict previously uncharacterized in vivo effects. Model simulations were used to inform designs of 60‐h and 10–21‐day in vivo exposures of adult fathead minnows ( Pimephales promelas ) to three or four test concentrations of the in vitro aromatase inhibitor imazalil ranging from 0.12 to 260 µg/L water. Consistent with an AOP linking aromatase inhibition to reproductive impairment in fish, exposure to the fungicide resulted in significant reductions in ex vivo production of 17β‐estradiol (E2) by ovary tissue (≥165 µg imazalil/L), plasma E2 concentrations (≥74 µg imazalil/L), vitellogenin (Vtg) messenger RNA expression (≥165 µg imazalil/L), Vtg plasma concentrations (≥74 µg imazalil/L), uptake of Vtg into oocytes (≥260 µg imazalil/L), and overall reproductive output in terms of cumulative fecundity, number of spawning events, and eggs per spawning event (≥24 µg imazalil/L). Despite many potential sources of uncertainty in potency and efficacy estimates based on model simulations, observed magnitudes of apical effects were quite consistent with model predictions, and in vivo potency was within an order of magnitude of that predicted based on in vitro relative potency. Overall, our study suggests that NAMs and AOP‐based approaches can support meaningful reduction and refinement of animal testing. Environ Toxicol Chem 2023;42:100–116. © 2022 SETAC. This article has been contributed to by U.S. Government employees and their work is in the public domain in the USA. Abstract : Key events in the adverse outcome pathway linking aromatase inhibition to reduced cumulative fecundity and spawning that were impacted following 60 h, 10 days, or 21 days of waterborne exposure to imazalil. Black shading indicates that no measurements were made. X indicates that activity was confirmed in vitro. Checkmark indicates that the measurement was made, with color bar indicating the lowest‐observed‐effect concentration.